Transparency, expectations, and forecasts - Andrew Bauer; Robert Eisenbeis; Daniel Waggoner; Tao Zha (European Central Bank (ECB), 2006)
In 1994 the FOMC began to release statements after each meeting. This paper investigates whether the public's views about the current path of the economy and of future policy have been affected by changes in the Federal Reserve's communications policy as reflected in private sector's forecasts of future economic conditions and policy moves. In particular, has the ability of private agents to predict where the economy is going improved since 1994? If so, on which dimensions has the ability to forecast improved? We find evidence that the individuals' forecasts have been more synchronized since 1994, implying the possible effects of the FOMC's transparency. On the other hand, we find little evidence that the common forecast errors, which are the driving force of overall forecast errors, have become smaller since 1994.
Keywords: E59; C33; 330; common errors; idiosyncratic errors; transparency; Geldpolitik; Politische Kommunikation; Frühindikator; USA